IMPACT OF ADVERTISING ON CONSUMER BEHAVIOUR - Dr. Archana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study was conducted to search out the impact of advertisement on consumer behaviour (N = 25). For this purpose, a self-explanatory questionnaire was wont to measure the results of advertisement. The results revealed that advertisement persuades the patron to a minimum of buy the merchandise once in a very lifetime. The model utilized in the commercial influenced the consumers more as compared to keyword / caption. Results also revealed that buyers considered advertisement as a reliable source of information as compared to others, (friend, neighbours, reference group) opinions. Advertisement can affect any income group, but expensive product and repetition of advertisement didn’t affect the purchasing attitude.